Brinquedoteca científica na universidade: uma experiência de extensão e ensino de Física junto à comunidade - Lopes, Deisy Piedade Munhoz [UNESP]; Stein-Barana, Alzira Cristina de Mello [UNESP]; Xavier, Leandro [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
The Scientific Educational Playroom is a space within the UniversidadeEstadual Paulista, Physics Department, and campus of Rio Claro, with theobjective of allowing the outer community to have access to scientificknowledge available in the university. Its main objective is to attend the studentsof the primary school their teachers, professors of the universities and otherpeople interested in this subject. It has a collection of the toys and theexperiments/toys, which Science activities for the primary school students areimplemented in a playful way throughout workshops with the students of thepublic and private schools of the region. The Sciences teacher may consult andreproduce its assortment since the toys and the experiments-toys wereassembled with low cost materials easily found in the market. As result theteacher has at his disposal an alternative didactic tool for enrichment andimproving of the activities of his classes. This article describes the beginning,the characteristics and the philosophy of the Scientific Educational Playroom,which is an extension project that was born from the challenge of guidingchildren to the pleasures of the knowledge throughout the science, particularlyPhysics.

La Jugueteca científica, es un espacio creado en la UNESP, Departamento de Física, Campus de Rio Claro, con el objetivo de permitir que la comunidad tenga acceso al conocimiento científico disponible en esa universidad. Se destina principalmente a estudiantes de educación básica, profesores de educación superior y otros interesados en el tema. La jugueteca tiene un acervo de juguetes y experimentos de juguetes, donde las actividades de Ciencias son trabajadas de forma dinámica con los estudiantes de los colegios públicos y particulares de la región, en las clases. El profesor de ciencias puede consultar y reproducir su acervo, pues está constituido por materiales de bajo costo y de fácil adquisición en el mercado. De esa forma, se dispone una herramienta didáctica alternativa para enriquecer las aulas del professor. En este artículo está descrito, la implementación, las características y la filosofia de la Jugueteca Científica, un proyecto e extensión que nació del desafio dellebar al niño al placer y al descubrimiento de la ciencia y en particular de la física.

A Brinquedoteca Científica, é um espaço criado na UNESP, Departamento de Física campus de Rio Claro, com o objetivo de permitir que a comunidade extra-muros tenha acesso ao conhecimento científico disponível na universidade. Destina-se principalmente a estudantes do Ensino Fundamental, seus professores, professores de Instituições de Ensino Superior e outros interessados no tema. Ela possui um acervo de brinquedos e brinquedos-experimentos, onde atividades de Ciências são trabalhadas de forma lúdica através de oficinas com estudantes das escolas públicas e particulares da região. O professor de Ciências pode consultar e reproduzir seu acervo, pois ele é constituído de material de baixo custo e facilmente encontrado no mercado. Deste modo, disponibiliza-se ao professor uma ferramenta didáticaalternativa para o enriquecimento de suas aulas. Neste artigo é descrita a implantação, as características e a filosofia da Brinquedoteca Científica, um projeto de extensão que nasceu do desafio de levar a criança ao prazer da descoberta através da Ciência e em particular da Física.
Scientific educational playroom at the university: an extension experiment in teaching physics to the community
Jugueteca científica en la universidad: una experiência de extensión y enseñanza de física en la comunidad
Keywords: Scientific educational playroom; Science teaching; University extension; Jugueteca; Educación de las ciencias; Extensión de la universidad; Exatas; Educação; Brinquedoteca; Ensino de Ciências; Extensão universitária